'The moon quivered like a snake': A medieval chronicler, lunar explosions, and a puzzle for modern interpretation. Issue 4 (December 2020) - Gasper, Giles E.M.; Tanner, Brian K.
Abstract: Despite some scepticism, the suggestion by Hartung in 1976 that the report in the chronicle of Gervase of Canterbury corresponded to a meteorite impact with the moon in 1178, creating the Giordano Bruno crater, retains considerable support, particularly in popular scientific writing. Nevertheless, a series of studies of images of the crater from orbiting satellites, although confirming its young geological age, have indicated that it was not created within recorded human history. In this paper, we examine astronomical entries in Gervase's chronicle relating to eclipses and conclude that, despite there being descriptions of miracles elsewhere in the manuscript, he himself was a reliable reporter of astronomical events. On this basis an alternative suggestion can be put forward for the splitting of the horns and writhing of the body of the new moon, reported to Gervase: atmospheric turbulence. Although general atmospheric turbulence has been previously dismissed as too small an effect, it is possible to show that the description is consistent with viewing the new moon through a column of hot air from a fire, at a moderate distance and out of the line of sight of the observers. This interpretation of the medieval evidence as credible but unrelated to a lunar event is consistent with twenty-first century lunar studies.